Production, Quality Test, and Activity Evaluation of Methanol Extract and Nanoparticles from Pluchea indica (L.) Leaves as Additives in Natural Soap against Propionibacterium acnes - Arsya Cahya Saputra; Elang Seta Wiratama; Fiyola Mayangsari; Via Divinka Oktafinantyas; Sri Handayani (Jurnal Kimia Sains dan Aplikasi, 2024)
Pluchea indica (L.) leaves, both in the form of extracts and silver nanoparticles, are known to exhibit antibacterial activity, but they have not been widely utilized in the health sector, especially in dermatology. This study aims to determine the quality test and antibacterial evaluation of natural soap formulated with methanol extract and nanoparticles of Pluchea indica (L.) leaves against Propionibacterium acnes. The synthesis of silver nanoparticles (AgNPs) was conducted using the reduction method, with AgNO3 as a precursor and methanol extract of Pluchea indica (L.) leaves serving as a reducing agent or bioreductor. Natural soap was produced through the cold process method, with a curing period of 3 to 4 weeks. Natural soap, derived from herbal ingredients, was made by combining NaOH, essential oils, and additives such as methanol extract and silver nanoparticles from Pluchea indica (L.) leaves. Quality tests were performed to assess moisture content (MC), fatty acid content, and pH levels. Antibacterial activity was assessed utilizing the well-diffusion method, with various sample concentrations ranging from 1.0 g/mL to 0.0625 g/mL. The quality test results for all soap samples met the Indonesian National Standard (SNI) requirements for acidity, free fatty acids, and moisture content. The bar soap without additives exhibited antibacterial activity, with a maximum inhibition zone of 14.26 mm (at 0.25 g/mL) after 15 hours. Natural soap with methanol extract of Pluchea indica (L.) leaf demonstrated an inhibition zone of 11.49 mm (at 0.0625 g/mL) after 15 hours, while nanoparticle soap exhibited an inhibition zone of 12.77 mm (at 0.25 g/mL) after 12 hours. In summary, all soap samples showed antibacterial activity, indicating the potential of Pluchea indica (L.) leaves as effective antibacterial agents.